Calf and arm circumference as simple markers for screening sarcopenia in patients with chronic liver disease. Issue 2 (28th November 2020) - Endo, Kei; Sato, Takuro; Kakisaka, Keisuke; Takikawa, Yasuhiro
Abstract : Aim: To prevent the progression of sarcopenia, early identification is important. We investigated the usefulness of sarcopenia screening tests using the arm and calf circumferences in patients with chronic liver disease. Methods: This was a single‐center cross‐sectional study based on data collected from a university hospital. We analyzed simple anthropometric data and sarcopenia‐related chemical data or imaging data between April and December 2019. Sarcopenia was defined according to the Japan Society of Hepatology guidelines. Results: In total, 661 patients participated. Low muscle mass and low muscle strength were found in 245 (37.1%) and 153 (23.1%) patients, respectively. Ultimately, 90 (13.6%) patients were diagnosed with sarcopenia. The sarcopenia group was significantly older and had a higher cirrhosis ratio and poorer liver function than the non‐sarcopenia group. The sarcopenia group had a significantly lower body mass index, arm circumferences and calf circumferences than the non‐sarcopenia group. A receiver operating characteristics analysis for diagnosing sarcopenia by arm and calf circumferences showed respective areas under the curve of 0.89 and 0.91 for men and 0.84 and 0.89 for women. The optimal cut‐off values of arm and calf circumferences were respectively determined to be 25.0 and 32.6 cm for men (sensitivity 88.4% and 83.7%; specificity 74.0% and 84.7%) and 22.7 and 32.1 cm for women (sensitivity 66.0% and 85.1%; specificity 90.0% and 81.3%). Conclusions: The arm and calf circumferences seem useful as simple surrogate markers for screening sarcopenia in patients with chronic liver disease.